The activity of glutamatergic neurons in the dorsal-ventral poles of the dentate gyrus regulates distinct phenotypes of depression in mice - Jinping Wang; Hongjie Li; Yusi Hua; Lanyu Zhang; Xiaoqin Jiang; Xinchuan Wei (Brain Research Bulletin)
Depression is a heterogeneous mental disorder. The dorsal and/or ventral dentate gyrus (DG) has been implicated in the pathophysiology of depression. However, it remains unclear whether the activities of glutamatergic neurons in the dorsal and ventral DG contribute to the heterogeneity of depression. In the present study, we conduct a series of depression-related behavior tests by activating or inhibiting the activity of glutamatergic neurons in the dorsal and ventral DG using chemical genetic methods. It is found that inhibiting the dorsal DG glutamatergic neurons induces social deficits, as well as learning and memory dysfunction, while activating them improves social behaviors and alleviated social deficits induced by chronic stress. Conversely, inhibiting the ventral DG glutamatergic neurons increases anxiety and despair-like symptoms, and activating them reduces anxiety and despair-like symptoms and alleviates these symptoms caused by chronic stress. Our study highlights the necessity of incorporating dorsoventral axis-specific analyses of DG in subsequent investigations to better understand the pathophysiological heterogeneity of depression.